DEVELOPMENT AND VALIDATION OF WEPP: UMOST (WEB-BASED ELECTRONIC PORTFOLIO PLATFORM: UNIVERSITY MARKETPLACE FOR SKILLS & TALENTS) - Bajao, Naomi A; Magpuyo, Sergio R; Edillon, April Jean S; Sarucam, Jae-an V; Tabotabo, Syd T (Journal of Agriculture and Technology Management; Vol 26 No 1 (2023): Vol 26 No 1 (2023): Journal of Agriculture and Technology Management (JATM) Volume 26 January - June 2023 Issue, 2023)
Portfolios are time-tested and teacher-trusted methods for assessing student learning. It is a tool for the students to keep their hard work. When they graduate they will be able to refer to their web-based portfolios with ease because they have been building them ever since entering college. The availability of graduates’ portfolios will become a ready marketplace for employers where they could find candidates who are a good fit for their needs based on validated reviews from faculty members who have witnessed the transformation of students from learners to qualified applicants. Employers and significant stakeholders will be able to provide comments and ratings to portfolios, which would provide valuable feedback to the university to upgrade instruction and other practices relevant to the various programs. The objective of this study is to develop and test a web-based system that will provide an avenue for students to actively maintain a portfolio where they can have a ready e-portfolio that they can use and update according to their professional journey and thus would aid in the graduate tracer endeavor of the university, serve as an added functionality to the university website, thereby increasing the website traffic, ranking, and visibility, allow employers to find qualified and good fit candidates based on validated reviews from faculty members, and aid instructional improvement based on students’ employability and employers’ feedback. The software application was developed using the Agile Method. Testing was done using the test cases identified. The needed features were successfully implemented and tested. Based on the survey on measuring the system’s usability with the USE Questionnaire, respondents were satisfied with the features and ease of the system of use and they agreed that the system is useful for the university.